JavaParty: Transparent remote objects in Java - Philippsen, Michael; et al. (Symposium on Principles and Practice of Parallel Programming, Workshop on Java for Science and Engineering Computation, 1997)
Java's threads offer appropriate means either for parallel programming of SMPs or as target constructs when compiling add-on features (e.g. forall constructs, automatic parallelization, etc.) Unfortunately, Java does not provide elegant and straightforward mechanisms for parallel programming on distributed memory machines, like clusters of workstations. JavaParty transparently adds remote objects to Java purely by declaration while avoiding the disadvantages of explicit socket communication, the programming overhead of RMI and many disadvantages of the message-passing approach in general. JavaParty is specifically targeted towards, and implemented on, clusters of workstations. It hence combines Java-like programming and the concepts of distributed shared memory in heterogeneous networks.
UnivIS-Import:2015-04-16:Pub.1997.tech.IMMD.IMMD2.javapa_4